Spatial Assessment of Polycyclic Aromatic Hydrocarbons in Streambed Sediments: Spatial Assessment of PAHs in Streambed Sediments - Ololade, I.A.; Lajide, L.; Oladoja, N.A. (Biological Sciences - PJSIR, 2009)
The occurrence and seasonal changes of polycyclic aromatic hydrocarbons (PAHs) in oil-contaminated sediment from selected oil areas of Ondo State, Nigeria were studied using gas chromatography–mass spectrometry. Six PAHs were identified and quantified with phenanthrene and carbazole, recording the highest and the least concentrations during the dry and wet seasons. Mean PAHs content ranged from 0.06 - 4.42 ìg/g and 0.09 - 6.0 ìg/g during the dry and the wet seasons, respectively. Significant correlations were observed (a = 0.05) between the two seasons but without significant mean difference (p = 0.05). For anthracene and phenanthrene, the compound toxic units (TU) were >> 1 and far exceeded the available consensus-based guidelines about the expected adverse effects. Results of the study call for further investigations especially with aquatic species due to the transfer of PAHs to humans via food chain.